ANALISIS PENGARUH BIAYA OPERASIONAL TERHADAAP PENDAPATAN NELAYAN DI KABUPATEN MIMIKA - Novesius Iry; Darius Sabon Rain (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2020)
This research aims to determine the impact of operating costs on revenue Fisherman in Mimika District. The research was conducted in Poumako, Eastern Mimika District, Mimika Regency using simple regression anolysis and classical assumption testing. The research method used in this research is the associative research method of explaining the causal relationship and the influence between the variables and the descriptive method of describing the objects and subjects in the research in fact. To determine the influence of operational cost variables on fishermen's revenues, the analytical instruments used in this study are simple regression analysis. The results of this research show that the operational costs have strong relationship and significant effect on the revenue of fishermen in Mimika district.